Dietary ethanol extract of mango increases antioxidant activity of pork - Araújo, Lina Raquel Santos; Watanabe, P. H.; Fernandes, D. R.; Maia, I. R. de O; Silva, E. C. da; Pinheiro, R. R. S.; Melo, M. C. A. de; Santos, E. O. dos; Owen, Robert; Trevisan, M. T. S.; Freitas, E. R. (Animal, 2021)
Ethanol extract of mango seeds (EEMS) are composed of several polyphenolic compounds with considerable in vitro antioxidant activity that can be used in pig feed and may contribute positively to meat quality characteristics. The aim of this study was to evaluate the effect of EEMS as a source of antioxidants in growing-finishing pig diets on meat quality, lipid stability, sulfhydryl groups non-proteinaceous (SG-NP), total phenolic compounds, total antioxidant potential and total antioxidant activity of meat after 1 and 7days of refrigeration storage. Thirty-two (60-day-old) barrows, weighing 20.20±1.34kg, were used in a randomized block design consisting of eight animals with four treatment regimens. Treatments consisted of: Control=no dietary antioxidant; butylated hydroxytoluene (BHT)=diet with 200ppm BHT; EEMS200=diet with 200ppm EEMS; EEMS400=diet with 400ppm EEMS. At 145days of age and average weight of 95.47±6.19kg, the animals were slaughtered and loin samples were collected and frozen before for qualitative analysis and evaluation of the effect of subsequent storage for 1 or 7days at 8°C on lipid stability, SG-NP, phenolic compounds, total antioxidant capacity and total antioxidant activity Meat from animals fed EEMS400 diet showed lower cooking loss (P<0.0001) and higher non-protein sulfhydryl groups, phenolic compounds and total antioxidant activity at both 1 and 7days of storage (P<0.0001) compared to the other treatments. Greater antioxidant capacity was observed at 1day storage in the meat of animals that consumed EEMS regardless of concentration when compared to the control group (P<0.01). The dietary inclusion of EEMS to pig diets is more effective at 400ppm in improving meat quality after cooking and antioxidant parameters of pork.